2022
DOI: 10.3389/fnagi.2022.782358
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research on the Effect of Melatonin on Postoperative Cognitive Dysfunction in Older Patients

Abstract: Postoperative cognitive dysfunction (POCD) is a common complication of the central nervous system in elderly patients after operation. It will prolong the length of stay, reduce the independence and quality of daily life, and increase the risk of death. However, at present, there is a lack of safe and effective ideal drugs for the prevention and treatment of POCD. Melatonin is one of the hormones secreted by the pineal gland of the brain, which has the functions of regulating circadian rhythm, anti-inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Univariate logistic regression analysis showed that age, coronary heart disease, cerebral infarction, ASA physical status classification, education level, preoperative MMSE and MOCA scores were predictors of POCD, which were similar to those previously reported. 9 , 23 , 33 , 34 , However, only age and duration of hospitalization were found to be independent risk factors for POCD in multivariate regression analysis. This indicated that the incidence of POCD increased with age and the duration of hospitalization increased, similar to the finding reported previously.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Univariate logistic regression analysis showed that age, coronary heart disease, cerebral infarction, ASA physical status classification, education level, preoperative MMSE and MOCA scores were predictors of POCD, which were similar to those previously reported. 9 , 23 , 33 , 34 , However, only age and duration of hospitalization were found to be independent risk factors for POCD in multivariate regression analysis. This indicated that the incidence of POCD increased with age and the duration of hospitalization increased, similar to the finding reported previously.…”
Section: Discussionmentioning
confidence: 81%
“…This indicated that the incidence of POCD increased with age and the duration of hospitalization increased, similar to the finding reported previously. 33 , 34 This may be because with the increase in age, the functions of various organs in the body of elderly patients tend to degenerate, the reserve capacity decreases, and the ability to withstand trauma such as surgery and anesthesia decreases. 35 The pharmacodynamics and pharmacokinetics of elderly patients may be decreased, making them more sensitive to drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that surgical trauma was one of the high risk factors for the cognitive dysfunction [ 12 ]. This was because that surgical trauma could cause the release of inflammatory cytokines, which played an important role in the development of cognitive dysfunction [ 13 ]. To investigate whether surgical trauma could affect the cognitive function in rats, in this study, SD rats, aged 18 months, underwent splenectomy to simulate the conditions of postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…52 In the human body, melatonin is a neuroregulatory hormone synthesized by pineal cells, which has the functions of regulating circadian rhythm, antioxidation, antiinflammation, scavenging free radicals, and immune regulation. 53 This catalytic protocol could allow the trifluoromethylation of various heteroarenes, including imidazopyridines, indoles, and thiophenes. The proposed mechanism involved Ni I -induced single-electron reduction of CF 3 I to generate the CF 3 radical.…”
Section: Late-stage Trifluoromethylation Of Arenes and Heteroarenes O...mentioning
confidence: 99%